Rejection Sensitivity, Self-Compassion, and Aggressive Behavior: The Role of Borderline Features as a Mediator - Sommerfeld, Eliane; Shechory Bitton, Mally (Frontiers in Psychology, 2020)
This study used mediation analyses to examine the assumption that the presence of borderline personality features mediates the relationship between rejection sensitivity (RS), self-compassion, and aggressive behavior. Sixty adults consisting of 31 participants diagnosed with borderline personality disorder and 29 participants with no diagnosis of borderline personality disorder were assessed for RS, self-compassion, aggressive behavior, and borderline personality features. Mediation was found for the total aggression score, anger score, and hostility score regarding both self-compassion and RS. Mediation was also found regarding RS and verbal and physical aggression, and regarding self-compassion and verbal and physical aggression. These findings provide evidence that the presence of borderline personality features is an important factor in explaining the associations linking RS and self-compassion to aggressive behavior. High RS and low self-compassion are associated with greater borderline personality features, which in turn relate to increased aggressive behavior.